Effectiveness of Lettuce Seed Encapsulation Containing Trichoderma Sp. in Control of Damping-off Disease - Sarah Hikmah Marieska; Sri Wiyatiningsih; Herry Nirwanto (Journal of Applied Agricultural Science and Technology, 2022)
Utilization of the antagonist fungus Trichoderma sp. in suppressing damping-off disease caused by Rhizoctonia solani can be done in various ways. One of them is through coating the seeds or encapsulation. This study aims to determine the effectiveness of lettuce seeds encapsulation containing Trichoderma sp. in suppressing damping-off disease through storage time of up to 12 weeks. The results showed that the use of talc and kaolin as a material carrier in encapsulation with 1 week of storage had the highest germination rate of 96%, while the lowest germination was at 12 weeks of storage, which was only 0-5%. The use of talc carrier showed a low percentage of infected seedlings, starting from storage time of 0 to 8 weeks. At 8 weeks of storage, the provision of carrier material in the form of talc showed the lowest percentage of infected seedlings, which was 40% on the last day of observation and had the highest value of effectiveness in controlling Rhizoctonia solani damping-off disease, which was 60%. Thus, seed encapsulation using a talc carrier was the most effective in suppressing damping-off disease up to 8 weeks of storage